Peran Artificial Intelligence (Ai) Bagi Guru Bimbingan Dan Konseling Dalam Konteks Filsafat Ilmu - Hardiyanti, Nita Qisthi; Prasetya, Akhmad Fajar (Jurnal Ilmu Bimbingan dan Konseling, 2025)
As technology advances, AI is emerging to assist in various aspects of human life. One area where AI is utilized is education, specifically guidance and counseling. AI is used to identify student needs, and counseling chatbots can assist in the implementation of established programs. The use of AI significantly enhances the performance of guidance and counseling teachers. Philosophy helps explain its epistemology, ontology, and axiology.